Semi-actively Implemented Non-linear Damping for Building Isolation Under Seismic Loadings - Zhu, Yun-Peng; Lang, Zi-Qiang; Kawanishi, Yosuke; Kohiyama, Masayuki (Frontiers in Built Environment, 2020)
It is well-known that semi-active solution can achieve building isolation with much less energy requirements than active solutions. Also, it has been shown in previous studies that compared to linear damping, non-linear damping performs better for building isolation under sinusoidal ground motions. The present study is concerned with the extension of the application of the semi-actively implemented non-linear damping to building isolation under seismic loadings. A two-degree-of-freedom (2-DOF) scaled building model is used for simulation studies. Experimental tests on a physical building model have been used to validate the effectiveness of the 2-DOF scaled building model in representing the behaviors of a physical building structure. The optimal design of the semi-actively implemented non-linear damping for building isolation under design seismic motions is then carried out using the 2-DOF scaled building model based on simulation studies. The results show that an optimal design of semi-actively implemented non-linear damping can improve the performance of building isolation under design seismic motions in terms of both absolute acceleration and inter-story drift.